5y+5(2+3)=4y+1

Simple and best practice solution for 5y+5(2+3)=4y+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5y+5(2+3)=4y+1 equation:


Simplifying
5y + 5(2 + 3) = 4y + 1

Combine like terms: 2 + 3 = 5
5y + 5(5) = 4y + 1

Multiply 5 * 5
5y + 25 = 4y + 1

Reorder the terms:
25 + 5y = 4y + 1

Reorder the terms:
25 + 5y = 1 + 4y

Solving
25 + 5y = 1 + 4y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-4y' to each side of the equation.
25 + 5y + -4y = 1 + 4y + -4y

Combine like terms: 5y + -4y = 1y
25 + 1y = 1 + 4y + -4y

Combine like terms: 4y + -4y = 0
25 + 1y = 1 + 0
25 + 1y = 1

Add '-25' to each side of the equation.
25 + -25 + 1y = 1 + -25

Combine like terms: 25 + -25 = 0
0 + 1y = 1 + -25
1y = 1 + -25

Combine like terms: 1 + -25 = -24
1y = -24

Divide each side by '1'.
y = -24

Simplifying
y = -24

See similar equations:

| 5x+10=4(x-2) | | t^2+6t-20=0 | | 3[4(4+1)]= | | -20-6r=-4(2r+3) | | t^2+6-20=0 | | 3[f(4)(4)+1]= | | -x-29=11+4x | | 3x=5(16) | | f(x)=0x^0 | | 3x*x=147 | | 14-2+11+3= | | 5x+15=8x+2 | | 2(d+3)=28 | | f(x)=2x^1+0x^0 | | 15+5z=-10 | | -24-4x=15-x | | 3(m+1)=13 | | f/x | | 2[x-3(0)]= | | 3(5x-2)=4(2x+6) | | 10(c+7)=90 | | -8y+9=13 | | -7(2f+8)=-126 | | f(x)=3x^2+2x^1+0x^0 | | X=(20-2x)*(40-2x) | | 14n+2=72 | | 10(s-5)=-98 | | x=(20-2x)(40-2x) | | f(x)=2senx | | x^4+x^3-8x^2+16x+6=0 | | 225=x^2-16x+68 | | 0=y^2-4y-1 |

Equations solver categories